PROPAGANDA ISSUES OF RACISM THROUGH SOCIAL MEDIA TO TRIGGER SOCIAL VIOLENCE IN PAPUA AND WEST PAPUA IN 2019 - M. Alfi Rajabi Nasution; Surya Wiranto (The Republic of Indonesia Defense University, 2020)
Racism events that took place in the Papua Student Dormitory, Surabaya, East Java had a long tail by causing mass protests and riots in Papua and West Papua from 19 August 2019 to 23 September 2019. Mass riots by Papuans and Papuan native students were triggered by the problem of spreading propaganda on the issue of racism on a massive scale through social media by exploiting the issue of racism that is happening in the city of Surabaya. This study uses propaganda theory, social conflict theory, and national security theory in analyzing these problems. This study uses qualitative research methods with a descriptive analysis approach. Sources of data obtained through interviews, observation, and literature studies. The results showed that the propaganda issue of racism was the cause of mass unrest and social conflict in Papua and West Papua; the propaganda issue of racism is very effective in achieving its broader goals of changing the attitudes and behavior of Papuan and Papuan indigenous students to be destructive and gaining local and international support by creating negative opinions as material to delegitimize and discredit the Government of Indonesia, and the propaganda issue of racism has resulted in damage to social relations with other Indonesian people and the potential for social conflict that can threaten national security.